The Role of Law in Sexual Violence Against Minors - Pudjiastuti, Diah; Alifatussyamsiah, Nurul; Nonik Novi Meilina (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
The rise of sexual violence or rape among minors, people flock to ask for criminal penalties for perpetrators of sexual violence. This clearly violates sexual morals, social morals and even religious morals and has a negative impact on child growth and development or puberty in today's children. Sexual violence is very rampant because victims are reluctant to report and they are forced to remain silent by perpetrators of sexual violence. In addition to providing psychological trauma, violence can also cause physical trauma and will make the victim haunted by excessive fear. Therefore, parents must know more about sexual violence that occurs in minors. The problems in this study are: what are the forms of sexual violence crimes that occur in children. What are the factors that encourage sexual violence or cheating on minors. And finally, what is the action or role of the law in tackling criminal acts of sexual violence that occur in minors?. Whether the role of the law is equal and can pay for the psychological and physical trauma of victims who lost their virginity due to violence during their teenage years. He should have received higher education and was in the process of achieving his goals, but was hampered because of outrage or what is happening in the present.